Nesting activity of the Loggerhead sea turtle, Caretta caretta, in Calabria: 2016-2020 reproductive seasons - DENARO, MARIA; MALITO, TERESA; MANCUSO, CARMELA; PARISE, GIOVANNI; URSO, SALVATORE (Mediterranean Marine Science, 2022)
The nesting activity of the loggerhead turtle along the coast of Calabria during five reproductive seasons (2016-2020) is presented. From May to August, survey methods were conducted using traditional observations on foot and utilizing additional innovative technologies, including electric fat bikes and drones. Monitoring was intensively focused on a key nesting area of approximately 40 km located on the southernmost Ionian coast of Reggio Calabria, and, for only the 2020 season, the area was extended an additional 40 km northeast. In the five nesting seasons, 419 female emergences were recorded, 192 of which were classified as nests. Overall, 65.1% (n = 125) of nests were found along the area regularly monitored in all nesting seasons. The maximum nesting activity was observed during July, and the mean nesting success was 45.8%. The average number of eggs for all seasons was 92.2 (n = 163; S.D.: ± 21.1; range: 39-160). The mean hatching and emergence success rates were 70.8% and 62.5%, respectively. The mean incubation period was 49 days (n = 122; S.D.: ± 5.4; range: 42-82). Considering previous data from the same area, our study shows an actual increase in nesting activity, probably due to the implementation of an effective monitoring method that includes the use of new technologies, which made it possible to expand the regularly monitored area, and a greater awareness campaign in recent years. Regarding the reproductive parameters, our data is similar to that reported for other Mediterranean nesting grounds.